ABCB1 Gene Is Associated With Clinical Response to SNRIs in a Local Chinese Han Population - Shan, Xiao-Xiao; Qiu, Yan; Xie, Wei-Wei; Wu, Ren-Rong; Yu, Yan; Wu, Hai-Shan; Li, Le-Hua (Frontiers in Pharmacology, 2019)
Background: The relation between the ATP-binding cassette sub-family B member 1 (ABCB1) gene and major depressive disorder (MDD) has been studied in a local Chinese Han population. MDD is associated with the rs2032582 (G2677T) and rs1128503 (C1236T) single-nucleotide polymorphism (SNPs) of ABCB1 but not with rs1045642, rs2032583, rs2235040, and rs2235015. This study aims to explore the potential correlations of therapeutic responses with selective serotonin reuptake inhibitors (SSRIs) and serotonin–norepinephrine reuptake inhibitors (SNRIs) in a local Chinese Han population. Methods: The study population included 292 patients with MDD. All patients were assessed at baseline, first, second, fourth, and sixth weeks according to the 17-item Hamilton Rating Scale for Depression (HAM-D17) to determine their therapeutic responses to SSRIs and SNRIs. Results: In the SSRIs therapy group, the genotype or allele distribution of six SNPs was not significantly different between responders and non-responders. In the SNRIs therapy group, only rs2032583 was associated with therapeutic response to SNRIs. The C allele of the ABCB1 rs2032583 polymorphism was negatively correlated with therapeutic responses according to logistic regression analysis. Conclusion: The ABCB1 gene polymorphisms may not be associated with therapeutic responses to SSRIs but not with SNRIs. The TT genotype could be a predictive factor of improved treatment responses to SNRIs in a Chinese population. These findings should be replicated in future studies with larger patient groups.